Integrating Brain-based Learning in the Science Classroom: A Systematic Review - Abiodun A Bada; Loyiso C Jita (International Journal of Pedagogy and Teacher Education, 2022)
Brain-based learning (BBL) has been described as an important pedagogy that can be effectively used to enhance different teaching methods or strategies. It uses essential principles from brain-based theory to alleviate the disadvantages inherent in traditional teaching methods to achieve classroom goals and objectives. The use of such learning has significant implications for the teaching and learning of science (biology, chemistry, mathematics, and physics) subjects at elementary and secondary school levels. In this review, we scrutinise and discuss the results from 25 peer-reviewed studies and underline the methodology and strategies used to advance the integration of brain-based learning within science classrooms. We make a meta-analysis systematic review of how such learning has been used in the science classroom, the success achieved, and the different constructs used to integrate it into elementary and secondary schools. The findings reveal that quasi-experimental studies have dominated the methods used in integrating brain-based learning in science classrooms. In addition, this type of learning topped the different constructs used in science classrooms, with its  integration mainly in relation to mathematics. It is concluded that the principles of brain-based learning pedagogy can be adequately used in science classroom instruction because they consider the uniqueness of each student’s brain. This paper therefore recommends appropriate and continuous integration of such learning in the science classroom, especially in subjects where integration is currently low.